PENELUSURAN SENYAWA SITOTOKSIK PADA KULIT BIJI NYAMPLUNG (Calophyllum inophyllum L.) DAN KEMUNGKINAN KORELASINYA SEBAGAI ANTIKANKER - Sri Rahayu Santi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Isolation and identification of active toxic compounds from nyamplung skin bean (Calophyllum inophyllumL). has been carried out. As much as 12,43 g of concentrated methanol extract was resulted from 1.0 kg dry powdernyamplung skin bean that was macerated using methanol. This extract was dissolved into methanol-water (7:3) andthen partitioned with n-hexane and chloroform respectively. The result of toxicity test to both extract showed thatchloroform extract was the most active toxic with LC50 = 239,88 ppmSeparation of chloroform extract using preparative thin layer chromatography (TLC) resulted in F5 fractionsthat was white yellowish as much as 52 mg and LC50 = 151,36 ppm. Infra red and UV-vis spectroscopy wereemployed in order to identify the F5 fraction. The result of identification showed that isolate was aldehidetriterpenoide compounds which had functional group like –OH (3429 cm-1), -CH aldehyde (2922,9 and 2852,9 cm-1),-CºC- (2360 cm-1), -C=O (1742,7 cm-1), -C=C- alkene(1637,0 cm-1), -CH3, -CH2 (1542,9, 1480,7, 1401,9 cm-1), -CO-(1090 cm-1), It showed absorbed at broad peaks at l(nm) (CHCl3): 254, 282, and 342,7.